2015
DOI: 10.1039/c5an00492f
|View full text |Cite
|
Sign up to set email alerts
|

A paper-based microbial fuel cell array for rapid and high-throughput screening of electricity-producing bacteria

Abstract: There is a large global effort to improve microbial fuel cell (MFC) techniques and advance their translational potential toward practical, real-world applications. Significant boosts in MFC performance can be achieved with the development of new techniques in synthetic biology that can regulate microbial metabolic pathways or control their gene expression. For these new directions, a high-throughput and rapid screening tool for microbial biopower production is needed. In this work, a 48-well, paper-based sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 49 publications
2
30
1
Order By: Relevance
“…The OCVs of the 8-well MFCs generates 1.7% variation with LB medium, which is far less than that of other MFC arrays (25%) and even our previous MFC arrays (2.5%) (Choi et al, 2015). This low percent deviation is mainly because of (i) consistent cathodic reactions from device to device by accessing freely available oxygen in the air and (ii) simplified device configuration, fabrication, and operation by integrating all components in a single sheet of paper.…”
Section: Resultscontrasting
confidence: 60%
See 3 more Smart Citations
“…The OCVs of the 8-well MFCs generates 1.7% variation with LB medium, which is far less than that of other MFC arrays (25%) and even our previous MFC arrays (2.5%) (Choi et al, 2015). This low percent deviation is mainly because of (i) consistent cathodic reactions from device to device by accessing freely available oxygen in the air and (ii) simplified device configuration, fabrication, and operation by integrating all components in a single sheet of paper.…”
Section: Resultscontrasting
confidence: 60%
“…This hypothesis is based on our extensive experience in biosensors and our recent series of breakthroughs in microfabricating bioelectrochemical systems, all of which suggest that using paper as a device substrate inherently produces favorable conditions for ease, control, rapidity, sensitivity, and parallel analysis of bacterial electrogenicity. Recently, we found that using a paper-based anode/cathode chamber, or reservoir, instead of the usual rigid materials allows for rapid adsorption of bacteria-containing liquid (Fraiwan et al, 2013, 2016; Fraiwan and Choi, 2014, 2016; Choi and Choi, 2015; Choi et al, 2015; Lee and Choi, 2015). This adsorption immediately promotes bacterial cell attachment to the electrode (e.g., biofilm formation), where bacterial respiration can then transfer electrons from the organic substrates to the electrode directly (mediatorless) or indirectly (mediator).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the past two decades, significant improvement on MFC has been demonstrated; for instance, the power density of microbial fuel cells have improved by more than four orders of magnitude, from 0.1 mWm −2 to 7.72 Wm −2 [4][5][6]. In order to improve the power density, a number of research have been performed, such as implementing the anode with high surface area to volume ratio [5,[7][8][9], investigating the performance of different species of exoelectrogen [10,11], investigating different MFC configurations, and investigating different operation conditions, including temperature, pH, flow rate, etc. [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%